Right Ventricular Maladaptation to Pressure Overload in Fischer Rats Is Associated With Profound Deficiency in Adenylate Kinase 1 and Impaired Ventricular Energetics. Issue 12 (24th October 2022) - Zelt, Jason G.E.; Cadete, Virgilio; Deng, Yupu; Godoy, Rafael; Cuillerier, Alexanne; Rowe, Katelynn; Abdul-Ghani, Mohammad; Megeney, Lynn; Burelle, Yan; Giulivi, Antonio; Stewart, Alexandre F.R.; Provencher, Steeve; et al.
Abstract : Background: We explored the mechanism of maladaptive right ventricular (RV) remodeling in Fischer compared with Sprague-Dawley (SD) rats exposed to pressure overload. Methods: Pulmonary hypertension was induced by injection of the VEGFR antagonist, SU5416, followed by a 3-week exposure to hypoxia (Sugen chronic hypoxia). In vivo oxidative metabolism was assessed by RV/left ventricle ratio of [ 11 C]acetate positron emission tomography clearance (kmono). Unbiased, global transcriptional and proteomic profiling was performed in Fischer and SD rats at baseline and after Sugen chronic hypoxia. Results: All Fischer rats succumbed to RV failure by 5 weeks, whereas SD rats showed preserved RV function and 88% survival beyond 9 weeks ( P <0.0001). Fischer rats exhibited increased oxidative metabolism at 4 weeks ( P <0.05) and impaired RV efficiency compared with SD (work metabolic index: 52±10 versus 91±27 mmHg·mL/cm 2, respectively; P <0.05), but no differences in mitochondrial complex activity. AK1 (adenylate kinase 1) was among the top 10 differentially expressed genes between Fischer and SD rats, with markedly lower RV expression in Fischer rats (FC: 3.36, P <0.05), confirmed by proteomic analysis and validated by Western blotting (>10-fold reduction, P <0.001). While whole-genome sequencing failed to reveal any coding region mutations in Fischer rats, there was a unique variant in a highly conserved upstream flanking region likely involved in the regulation of AK1 expression. Conclusions: Therefore, Fischer rats exhibit profound AK1 deficiency and inefficient cardiac energetics likely related to reduced adenosine triphosphate shuttling from the mitochondria to the contractile fibers. This represents a novel mechanism for RV failure in response to chronic increases in afterload.